Auditing the Academic Information System of the Indonesian Christian University Toraja Using the Cobit 5 Framework - Ferayanti Boas Gallaran; Chrismesi Pagiu; Srivan Palelleng (LPPM, 2022)
Rapid technological developments make all sectors vying to use the latest technology. No exception in the field of education, technology is a basic need to support the teaching and learning process. One example of the technology used by UKI Toraja is the UKI Toraja Ecampuz Academic Information System. This system has been in use since the end of 2018 until now. Since the use of the Ecampuz UKI Toraja Academic Information System, it has provided many benefits, especially for its users, namely lecturers, students and employees. However, a system is a man-made product, so nothing is perfect, neither is the academic system used by UKI Toraja. Based on this hypothesis, this study aims to audit the Ecampuz UKI Toraja Academic Information System using the COBIT 5 framework by focusing on the domains of Evaluating Governance, direction, monitoring (EDM), Align, Plan and Organize (APO), Build, Acquire, and Implement (BAI), Deliver, Service and Support (DSS), Monitor, Evaluate, Assess (MEA) so that the Academic Information System can support the progress of the University effectively and efficiently.The final result of this research is that the highest matrix value is 0.932 in APO7 and APO11, while the lowest matrix value is 0.546 at EDM4 and APO4. This means that in managing resources and quality at SIA UKI Toraja has been good but still lacking in optimizing resources and innovation at SIA UKI Toraja (Ecampuz)